Pelaksanaan Penelitian Kemasyarakatan (Litmas) Dalam Perkara Anak Berkonflik Dengan Hukum Di Bapas Pati - Claodia Narasindhi; Iskandar Wibawa (UNES Law Review, 2023)
Children are the successors of the life of society and the state as the next generation of the nation. Therefore, the criminal justice process for children does not merely look for proof of wrongdoing committed by the child. However, in this process there needs to be a study of the factors that cause a child to commit a criminal act. UU No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA) is one of the bases that regulates special treatment or actions that must be given to children who conflict with the law. The community research reports (LITMAS) are an important instrument in the juvenile criminal justice system. All activities of law enforcement officers carried out in the context of juvenile justice must be based on the welfare of the child and the interests of the child. The aim of juvenile justice cannot be separated from the main aim of realizing children's welfare which is basically an integral part of social welfare. The juvenile justice process, from the investigation process to the imposition of sanctions and placement in correctional institutions, must consider the Community Research Report (LITMAS)